Impact of Metastasectomy in the Multimodality Approach for BRAF V600E Metastatic Colorectal Cancer: The Mayo Clinic Experience. (13th September 2017) - Johnson, Benny; Jin, Zhaohui; Truty, Mark J.; Smoot, Rory L.; Nagorney, David M.; Kendrick, Michael L.; Kipp, Benjamin R.; Grothey, Axel
Abstract : Background: BRAF V600E mutations are present in 8%–10% of patients with metastatic colorectal cancer (mCRC) and portend poor prognosis. This study investigated the impact of metastasectomy for patients with BRAF V600E mCRC. Subjects, Materials, and Methods : Using prospective clinical and molecular data, patients with BRAF V600E mCRC were analyzed for clinical characteristics and survival. Statistical analyses utilized the Kaplan‐Meier method, log‐rank test, and Cox proportional hazard models. Results: Fifty‐two patients were identified between July 1, 2008, and January 4, 2016. Patient characteristics included median age 65 years, 61% female, Eastern Cooperative Oncology Group performance status ≤1, 71% with right‐sided tumors, and 28% with liver‐limited metastasis. In the first‐line setting, 7% (4/52) received fluorouracil, leucovorin, oxaliplatin, and irinotecan (FOLFOXIRI)/bevacizumab (BEV) and 81% were treated with doublet chemotherapy consisting of fluoropyrimidine, oxaliplatin, and BEV. Median overall survival (OS) for all 52 patients was 25 months with median progression‐free survival (PFS) of 9.3 months. With median follow‐up of 18.3 months, 21 patients underwent metastasectomy with longer OS (29.1 months vs. 22.7 months, hazard ratio [HR] = 0.33; confidence interval [CI], 0.12–0.78; p  = .01) and PFS (13.6 months vs. 6.2 months, HR = 0.53, CI, 0.28–0.97; p  = .03) compared with the non‐metastasectomy cohort. In multivariate analysis, metastasectomy remained significant for improved survival outcomes (HR = 0.52; 95% CI, 0.07–1.02; p  = .02). Median disease‐free survival after metastasectomy was 9.7 months (95% CI, 5.5–19.5). Two patients remain disease‐free at the time of last follow‐up, with one patient without relapse for greater than 2 years (28.9 months). Conclusion: Multimodality therapy incorporating metastasectomy for BRAF V600E mCRC should be considered and might be associated with improved overall survival in select patients. Implications for Practice: BRAF V600E metastatic colorectal cancer (mCRC) represents an extremely difficult molecular subset of colorectal cancer to treat. To date, this subset remains refractory to standard chemotherapies, prompting extensive clinical investigation regarding novel treatment approaches and targeted modalities. While the use of metastasectomy for expanded RAS wild‐type and RAS mutated mCRC has resulted in improved overall survival for select patients, utilization of metastasectomy in patients with BRAF V600E mCRC remains controversial. This article explores the authors' experience with BRAF V600E mCRC to ascertain whether a multidisciplinary approach incorporating metastasectomy for well‐selected patients improves overall survival. Abstract : BRAF V600E mutations are present in 8%–10% of patients with metastatic colorectal cancer (mCRC). This study investigated the impact of metastasectomy for patients with BRAF V600E mCRC.